The Effect Of Work Conflict And Job Stress On Employees Performance With Organizational Commitment As Intervening Variable - Kurniawan, Rizky Budi; Sularso, R Andi; Titisari, Purnamie (Jurnal Manajemen dan Kewirausahaan, 2018)
Jatiroto Sugar Factory is the largest business unit owned by PTPN XI, the performance of Jatiroto Sugar Factory is the foundation of the company's survival because it has the largest sugar production capacity among other business units.This study aims to analyze the effect of work conflicts, work stress, organizational commitment and employee performance at Jatiroto Sugar Factory. This research is an explanatory research. The population in this study are employees of permanent status and has worked at least 2 years as many as 150 people.The results shows that : 1) Work conflicts have significant effect on organizational commitment of employees; 2) Work stress significantly influences organizational commitment of employees; 3) Work conflicts significantly affect employee performance; 4) Work stress had a direct but not significant effect on employee performance; 5) Organizational commitment has a significant effect on employee performance at Jatiroto Sugar Factory.Â https://doi.org/10.26905/jmdk.v6i1.1985